The space disaster - McElligott, Matthew (McElligott, Matthew. Mad Scientist Academy., 2017)
Dr. Cosmic's class of clever monsters experience gravity and weightlessness, a close encounter with an asteroid, and what it's like being on the other planets of the solar system, in this blend of adventure and exploration.